Pengaruh Terpaan Media dan Daya Tarik Destinasi Wisata terhadap Minat Berwisata - T. Titi Widaningsih; Yuli Nugraheni; E. Nugrahaeni Prananingrum; Arry Rahayunianto (Fakultas Ilmu Komunikasi UKWMS, 2020)
The world has entered the industrial era 5.0, when all aspects of human life are controlled by information technology. Society is changing and moving fast with technology to achieve a more meaningful life. The tourism industry has also developed following the development of industry 5.0 which is marked by the full digitization of the tourism sector. The way tourists travel is changing. The tourists will start their journey by looking for or seeing a variety of information (look), then proceed with the second step, namely ordering a tour package that is of interest (book) and the next part is the final stage, which is paying online (pay). Communication technology has changed the behavior of the tourism market towards digital. Tourist behavior is increasingly mobile, personal and interactive. Tourists can easily get tourist information with the availability and easy access to communication networks. Media with various tourist information have an influence on tourists to travel. In addition to communication media, the attractiveness of tourist destinations also affects tourists' choice of visiting tourist destinations. The purpose of this study was to determine the effect of media exposure and the attractiveness of tourist destinations on tourism interest. The research was conducted in the Betawi Cultural Tourism Area Setu Babakan, South Jakarta, Indonesia. The results showed that media exposure and tourist attraction influenced the interest in visiting tourist destinations.